2024
DOI: 10.3390/pr12020383
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heterogeneous Sulfated Acid Photocatalysts and Irradiation of Ultraviolet Light on the Chemical Conversion and Characteristics of Antifreeze from Bioglycerol

Cherng-Yuan Lin,
Yun-Chih Chen

Abstract: The purity of crude glycerol, a by-product of biodiesel production, may be as low as 50%. Thus, it has relatively low economic value without previously applying adequate physical purification or chemical conversion processes. A solid-state sulfated acid photocatalyst, TiO2/SO42- was prepared in this study to catalyze the chemical conversion of bioglycerol with acetic acid to produce an antifreeze of glycerine acetate to improve the low-temperature fluidity of liquid fuel. The experimental results show that sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…A molar ratio of acetic acid/glycerol higher than 8 may retard the dehydration condensation reaction between -COOH radicals in the acetic acid molecules and OH − radicals in diacylglycerol (DAG) to produce a reverse reaction [22], resulting in lower TAG formation, and thus, a higher freezing point at a molar ratio of 9. Lin and Chen [23] also found that the TAG formation decreased from the highest amount of 40.41% to 34.63% when the molar ratio of acetic acid/glycerol increased from 8 to 9. Under UV irradiation on the solid-state strong acid photocatalyst surface, the photocatalyst will form an electron-electron hole pair.…”
Section: Analysis Of Fuel Characteristics Of Blended Biodieselmentioning
confidence: 89%
“…A molar ratio of acetic acid/glycerol higher than 8 may retard the dehydration condensation reaction between -COOH radicals in the acetic acid molecules and OH − radicals in diacylglycerol (DAG) to produce a reverse reaction [22], resulting in lower TAG formation, and thus, a higher freezing point at a molar ratio of 9. Lin and Chen [23] also found that the TAG formation decreased from the highest amount of 40.41% to 34.63% when the molar ratio of acetic acid/glycerol increased from 8 to 9. Under UV irradiation on the solid-state strong acid photocatalyst surface, the photocatalyst will form an electron-electron hole pair.…”
Section: Analysis Of Fuel Characteristics Of Blended Biodieselmentioning
confidence: 89%